2018
DOI: 10.1016/j.energy.2018.03.157
|View full text |Cite
|
Sign up to set email alerts
|

Study and simulation of the energy performances of a grid-connected PV system supplying a residential house in north of Algeria

Abstract: Worldwide, building is one of the most consuming energy sectors which are contributing significantly to the greenhouse effect, climate change and negative environmental impact. In Algeria, building sector is responsible of about 42% of the final energy consumption, with about 35% in the residential houses and 6% in the tertiary. This consumption is still in expansion, due to mainly on an exceptional growth of population and urbanism. The main objective of this paper is to study and assess the contribution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…• Description du modèle Sandia Un modèle comportemental développé par Sandia National Laboratories (SNL) fournit un moyen de prédire la puissance de sortie AC à partir de la puissance d'entrée DC [20], ce modèle a été utilisé dans nombreux travaux d'analyse de performance des systèmes PV [9,16,21,22].…”
Section: Validation Du Modèle Simplifiéunclassified
“…• Description du modèle Sandia Un modèle comportemental développé par Sandia National Laboratories (SNL) fournit un moyen de prédire la puissance de sortie AC à partir de la puissance d'entrée DC [20], ce modèle a été utilisé dans nombreux travaux d'analyse de performance des systèmes PV [9,16,21,22].…”
Section: Validation Du Modèle Simplifiéunclassified
“…2. This model is composed of numbers of silicon cells which operates as a current source, also these cells are assembled with each other in a large unit to form PV panels which are grouped in arrays [25]. In general, number of cells are used in a particular series or parallel arrangement to control the generated PV current or by change the numbers of the cells in each panel.…”
Section: Pv Cell Modelmentioning
confidence: 99%
“…The analysis concluded that it is profitable to install home wind turbines because it is able to cover the demand for electricity in various weather conditions. Another example of research is a study by Laib et al [2] in an apartment house in the north of Algeria. The study covered a household where photovoltaic panels produce electricity on sunny days, and when the weather conditions are unfavourable, energy is taken from the grid.…”
Section: Introductionmentioning
confidence: 99%